Association between Medial Longitudinal Arch with Static and Dynamic Balance among Recreational Badminton Players - Chang Zhong Han; Ambusam Subramaniam; Fairus Fariza Zainudin; Rajkumar Krishnan Vasanthi (OVS LLC, 2022)
The study purpose was to examine the association between the Medial Longitudinal Arch (MLA) and balance among recreational badminton players. Materials and methods. Total of 48 recreational badminton players aged 18-40 (24 males and 24 females) were recruited. Navicular Drop Test (NDT), Single Leg Stance Balance Test (SLSBT) and Modified Star Excursion Balance Test (mSEBT) were assessed on both dominant and non-dominant leg. Participant's foot type was categorized using NDT scores according to difference of navicular height in weight bearing and relax sitting; static balance was grouped based on the time (seconds) the players were able to maintain balance during the SLSBT; and dynamic balance was grouped based on the percentage of distance reached in mSEBT. Results. The study results revealed a significant association between the MLA of dominant (p<0.05) and non-dominant leg (p=0.02) with static balance among recreational badminton players. However, there is no significant association between the MLA of dominant (Anterior: p=0.39; Posteromedial: p=0.34; Posterolateral: p=0.98) and non-dominant leg (Anterior: p=0.39; Posteromedial: p=0.54; Posterolateral: p=0.07) with dynamic balance. Conclusions. The current study concludes that there is a significant association between the MLA and static balance. However, no changes were seen in dynamic balance. Thus, coaches and trainers may look into the MLA of players to improve their static balance, which can further improve their sports performance. Future studies are recommended to examine the effects of dynamic balance in more depth with increased sample size.